(untitled) (Diametros, 2011)
This paper presents Ernst Cassirer’s critical philosophy and its multidimensionality, which makes it possible link the quantitative methodology of the exact sciences with non-quantitative methodology of the humanities. In the text I undertake the task of presenting the thinker as a neo-Kantian who follows both the mathematical and physical path of Kant and the antinaturalistic path of Geistesgeschichte, as befits Cassirer’s as both a philosopher and a historian of philosophy who builds his own project of the philosophy of culture. I also point to an important issue for Cassirer, the matter of the historic consciousness of Wilhelm Dilthey who allows for the interpretation of the problem of man in the context – as Paczkowska-Łagowska puts it – of the "historical continuity of the tradition".